Developing a virtual reality application for online arts and psychomotor therapies using action research - Nathalie Jans; Nathalie Jans; Hans Wouters; Joep Kolijn; Suzanne Haeyen; Suzanne Haeyen; Suzanne Haeyen (Frontiers in Virtual Reality)
BackgroundVirtual Reality (VR) holds much promise for online offering of arts and psychomotor therapies. As these therapies use bodily experiences, expressive/artistic media, materials, movement, music, and (role) play, VR is more suitable than online/video consultations.ObjectivesThis study was set up to improve VR possibilities for arts and psychomotor therapies, with the primary aim of redeveloping and rebuilding a VR application.MethodsUsing Lewin’s paradigm of Action Research in conjunction with the Lean Start up Method to develop Minimal Viable Products, we developed and built the Virtual Reality Health Experience (VRhExp), a full body multiplayer VR space providing online arts and psychomotor therapies. The Action Research concerned a one-year co-creation project involving 17 arts and psychomotor therapists (Mean age 44.1 years, SD 11.3) together with input from media designers in education and technical VR developers. The Action Research consisted of five cycles. All cycles were held in groups.ResultsWe redeveloped an initial multiplayer full body VRhExp application based on users’ preferences, and ideas. Our participants reported becoming more proficient in using VR than at the start. Training and workshops held with arts and psychomotor therapists enhanced their knowledge of and skills in using the VRhExp. They provided input for the patient journey which was then used to develop a roadmap with the prerequisites for the implementation of the VRhExp in clinical practice. All participants indicated that the current version of VRhExp is not yet ready for use in clinical practice but appreciated that a great step forward had been made. Of the arts and psychomotor therapists who participated in the workshops, four out of five acknowledged the potential of acting and experiencing with the VRhExp (79%).ConclusionThe VRhExp is a promising tool for patients with psychological disorders as it enables the continuity of care provision by therapists. The VRhExp is a first step towards developing a broader landscape for offering online experiential arts and psychomotor therapies.